Proteomic and morphological analysis of bone and articular cartilage changes in osteoarthritic rabbits supplemented with Edible Bird’s Nest (EBN) - Sulaiman, Sharifah Zakiah Syed; Umran, Nor Shahira Solehah; Mohamed, Suhaila; Abu, Jalila; Ng, Angela Min Hwei; Lau, Benjamin Yii Chung; Lai, Kok Song; Ilias, Nazhan; Lau, Seng Fong; Ajat, Mokrish (Penerbit UTM Press, 2024)
This study is aimed at assessing the effects of Edible Bird’s Nest (EBN) on subchondral bone, articular cartilage and the expression of proteins in synovial fluid by micro-CT evaluation and histological analysis. 54 New Zealand white rabbits were induced by intra-articular injection of monosodium iodoacetate (8 mg) and divided into four groups: negative control (n=9): non-treated osteoarthritis; positive control (n=15): OA + diclofenac sodium 2 mg/kg daily orally; low dosage (n=15): OA + 75 mg/kg hydrolyzed EBN; and high dosage (n=15): OA + 150 mg/kg hydrolyzed EBN. The joints were harvested and subjected to micro-CT analysis and histological evaluation, and the synovial fluid was subjected to LCMS/MS analysis. Micro-CT analysis showed an increase in bone volume and a decrease in total porosity in the treatment group that showed bone integrity improvement. Histopathological results revealed comparable changes between the positive control group and the EBN treatment group. There was upregulation of proteins involved in the resolution of inflammation and downregulation of proteins associated with the bone resorption process. Morphology evaluation showed that EBN supplementation has a bone-improving effect by inhibiting osteoclastic activity. Protein expression showed chondroprotection and bone improvement through the action of several proteins via various signaling pathways. The morphological and molecular findings suggest the potential use of EBN as beneficial alternative for osteoarthritis treatment by improving bone quality and modulating inflammatory responses.